Food poisoning outbreaks among schoolchildren in Terengganu and their associated factors - Nur Baizura Aini Abdullah; Ahmad Filza Ismail (Penerbit Universiti Kebangsaan Malaysia, 2021)
Food poisoning is a public health problem in Malaysia and among the top five communicable diseases in Malaysia. This study aimed to determine the proportion of food poisoning cases involving schoolchildren in Terengganu in 2016 and their associated factors. This was a cross-sectional study using secondary data collected from 21 food poisoning outbreaks among schoolchildren in Terengganu in 2016. The proportion of food poisoning outbreaks involving schoolchildren in Terengganu in 2016 was 63.6%. Ministry of Education (MOE) school had contributed to 95.3% of outbreak cases, 81% occurred at secondary school and 57.1% involved school located in urban district. Poultry (61.9%) was the most common food vehicle, and Salmonella spp. (52.4%) was the most common microbial etiological agent. Urban district schools had the adjusted odds (aOR=1.803; 95% CI: 1.435,2.267; p < 0.001) compared with rural district schools. Non-MOE schoolchildren were more likely to be involved in school food poisoning (aOR= 4.439; 95% CI: 2.690,7.177; p <0.001) compared with MOE schoolchildren. Moreover, egg consumption was 4.6 times (aOR=4.627; 95% CI: 1.779,12.035; p=0.002) more likely to be associated with school food poisoning outbreaks in Terengganu in 2016 compared with rice consumption. Cross-contamination (aOR=0.445; 95% CI: 0.445,0.231; p=0.015) was less likely to be linked to school food poisoning compared with inadequate cooking and reheating. Food poisoning among schoolchildren in Terengganu has been associated with non-modifiable factors, such as school district location, and modifiable factors, such as food vehicles and critical control points. Health education on food safety, food handling, strict hygiene practice and clean canteen environment need to be strengthened.